Ion migration resistant electronic grade glass fiber cloth and preparation method thereof
Combined with high temperature retardation by using a composite coupling agent system of allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent and phenyl trimethoxy silane coupling agent in the preparation of electronic grade glass fiber cloth The steps of slurry and water-fiber processing solve the problem of insufficient bonding strength between glass fiber and resin, and significantly improve the ion mobility and heat resistance of copper clad plate.
Patent Information
- Application Number
- CN202411562841.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The bonding strength between the glass fiber and the resin interface of the existing electronic grade fiberglass cloth is insufficient, resulting in the separation of resin and glass fiber, affecting the insulation reliability and ion mobility of printed circuit boards.
The composite coupling agent system adopts allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent and phenyl trimethoxy silane coupling agent, through high-temperature desizing, water fiber boiling treatment, treatment liquid impregnation and The steps of treating liquid fiber opening treatment can improve the interface bonding strength and resin wetting properties between the glass fiber cloth and the resin.
The interface bonding strength between the glass fiber cloth and the resin and the wetting properties of the resin are significantly improved, and the ion mobility and heat resistance of the copper clad plate are enhanced.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of glass fiber cloth, and in particular relates to an ion migration resistant electronic grade glass fiber cloth and a preparation method thereof. Background Art
[0002] Electronic grade glass fiber cloth is woven from electronic grade glass fiber yarn and is mainly used in the manufacture of copper clad laminates, which are the dedicated basic materials for printed circuit boards (PCBs). The quality of electronic grade glass fiber cloth is an important factor affecting the appearance quality of copper clad laminates and the processing performance and physical and chemical properties of printed circuit boards. As the manufacturing technology of printed circuit boards develops towards micro-apertures, fine lines, high-density wiring and high-layers, the requirements for substrate heat resistance, low expansion coefficient, high dimensional stability, low dielectric loss, etc. are constantly increasing. The hairiness of electronic grade glass fiber cloth, resin impregnation and heat resistance of the board have become the focus of attention for copper clad laminates.
[0003] At present, the production methods of electronic-grade glass fiber cloth often have the following problems: the interface bonding strength between glass fiber and resin compound is not strong enough, resulting in delamination of resin and glass fiber, which may cause the printed circuit board to explode or ion migration, thus affecting the insulation reliability of the printed circuit board; in addition, due to the dual influence of the fiber opening effect of glass fiber cloth and the poor resin wettability of electronic-grade glass fiber cloth, it is difficult for the resin to completely penetrate between the fibers inside the yarn. After the circuit board is made, the gaps between the fibers in the yarn will cause ion migration, resulting in a short circuit in the circuit board.
[0004] Patent application CN115354494B discloses a production method of thin electronic-grade glass fiber cloth, comprising the following steps: sizing the electronic-grade glass fiber yarn, applying the sizing agent evenly to the yarn of each glass fiber yarn, winding the glass fiber yarn on the warp beam, and sizing the glass fiber yarn; weaving the sized glass fiber yarn into thin glass fiber cloth by using an air jet loom after sizing; desizing the woven thin glass fiber cloth at high temperature once, desizing the thin glass fiber cloth after the high-temperature desizing once at high temperature twice, desizing the sizing agent to less than 0.05%, and obtaining the desizing thin glass fiber cloth; opening the desizing thin glass fiber cloth, and impregnating the opened glass fiber cloth with a surface treatment agent silane coupling agent to obtain the thin electronic-grade glass fiber cloth. The patent obtains thin electronic-grade glass fiber cloth, but there are still problems such as insufficient interface bonding strength between the glass fiber cloth and the resin and poor ion migration resistance. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide an electronic-grade glass fiber cloth resistant to ion migration and a preparation method thereof. The electronic-grade glass fiber cloth has the characteristics of high interface bonding strength between the electronic-grade glass fiber cloth and the resin and good resin wettability. The copper clad laminate prepared thereby has good resistance to ion migration and excellent heat resistance.
[0006] In order to achieve the above object, according to one aspect of the present invention, a method for preparing an ion migration resistant electronic grade glass fiber cloth is provided, comprising the following steps:
[0007] (1) The sized warp yarns are evenly wound on the warp beam for sizing;
[0008] (2) Put the sized warp beam on the loom, insert the weft on the loom, and weave the rough glass fiber cloth according to the warp and weft density;
[0009] (3) desizing the crude glass fiber cloth at high temperature, and obtaining the desizing glass fiber cloth after cooling;
[0010] (4) subjecting the desized glass fiber cloth to water fiber opening treatment, primary drying, treatment liquid immersion treatment, secondary drying, treatment liquid fiber opening treatment and tertiary drying in sequence to obtain the ion migration resistant electronic grade glass fiber cloth; wherein the treatment liquid contains allyl epoxy polyoxyethylene polyether modified amino silane coupling agent and phenyl trimethoxy silane coupling agent in a mass ratio of 2-3:1.
[0011] In the present invention, in step (1), the sizing warp yarns are uniformly wound on the warp beam for sizing. Preferably, the sizing agent is uniformly applied to the warp yarns by a sizing machine, and then the sizing warp yarns are uniformly wound on the warp beam. The sizing agent used in the present invention includes starch esters, PVA and acrylic esters.
[0012] In the present invention, in step (2), the sizing warp beam is placed on a loom, and the weft is inserted on the loom to interweave the glass fiber cloth into a rough product according to the warp and weft density. Preferably, the warp density is 120 strands / 25 mm, and the weft density is 64 strands / 25 mm.
[0013] In the present invention, in step (3), the crude glass fiber cloth is subjected to high temperature desizing, and after cooling, the desizing glass fiber cloth is obtained. In the present invention, in step (3), the desizing temperature is 380-400°C, and the time is 30-40 minutes.
[0014] In the present invention, in step (4), the desized glass fiber cloth is sequentially subjected to water fiber opening treatment, primary drying, treatment liquid immersion treatment, secondary drying, treatment liquid fiber opening treatment and tertiary drying to obtain the ion migration resistant electronic grade glass fiber cloth. In the present invention, the treatment liquid contains an allyl epoxy polyoxyethylene polyether modified amino silane coupling agent and a phenyl trimethoxy silane coupling agent in a mass ratio of 2-3:1. It can be understood that the mass ratio can be any specific value of 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1 or any value within the range of 2-3:1. Preferably, the treatment liquid contains an allyl epoxy polyoxyethylene polyether modified amino silane coupling agent and a phenyl trimethoxy silane coupling agent in a mass ratio of 2.5-3:1. The present invention needs to strictly control the mass ratio of the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent and the phenyl trimethoxysilane coupling agent. Only when the mass ratio of the two is controlled within a suitable range, the synergistic effect of the two is optimal. If the mass ratio of the two is high, that is, the relative content of the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is high, the number of flexible long chains is too large, and it is easy to accumulate and entangle too many molecular chains at the interface of the glass fiber cloth and the resin, and it is easy to produce a weak interface, thereby reducing the interface bonding strength. If the mass ratio of the two is low, that is, the relative content of the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is low, the stacking and entanglement effect of the flexible long chain molecular chain at the interface is not obvious, and the number of active functional groups in the system is small, resulting in a reduction in the interface bonding strength.
[0015] The inventors found that most of the coupling agents used in the existing glass fiber cloth preparation process are complex coupling agent systems with more than two short molecular chains. The coupling agent molecular chains in these complex coupling agent systems are relatively short and the number of active functional groups in the molecular structure is limited. Therefore, the improvement of the interface performance between the glass fiber cloth and the resin is limited, especially the interface bonding strength is not high. Based on this, the inventors obtained a long-chain coupling agent by reacting allyl epoxy polyoxyethylene polyether and aminosilane coupling agent, and then compounded the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent and phenyltrimethoxysilane coupling agent in proportion. The interface bonding strength and resin wettability of the glass fiber cloth and the resin can be greatly improved, and the corresponding copper clad laminate has significantly improved ion migration resistance and heat resistance. On the one hand, since the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent has a longer molecular chain and a larger number of active functional groups, it is more conducive to bonding the interface between the glass fiber cloth and the resin; at the same time, these flexible long molecular chains can also produce physical entanglement at the interface, further improving the interfacial bonding strength, thereby improving the ion migration resistance. On the other hand, the phenyl trimethoxy silane coupling agent has a shorter molecular chain and contains a phenyl group. After compounding with the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent in proportion, the two synergistically enhance the system, so that the system has excellent interfacial bonding strength, ion migration resistance and heat resistance.
[0016] Preferably, the treatment liquid includes 0.2-1.5% allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent, 0.1-0.5% phenyl trimethoxy silane coupling agent, 0.1-1.5% acetic acid and the balance of water by mass percentage. In the present invention, in the treatment liquid, the mass percentage of allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is 0.2-1.5%, and its mass percentage can be any specific value of 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt% or any value within the range of 0.2-1.5%. More preferably, the treatment liquid includes 0.5-1.5% allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent by mass percentage. In the present invention, the aminosilane coupling agent is 3-aminopropyltrimethoxysilane.
[0017] In the present invention, in the treatment liquid, the mass percentage of phenyltrimethoxysilane coupling agent is 0.1-0.5%, and its mass percentage can be any specific value of 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% or any value in the range of 0.1-0.5%. More preferably, the treatment liquid includes 0.25-0.5% phenyltrimethoxysilane coupling agent by mass percentage.
[0018] In the present invention, the mass percentage of acetic acid in the treatment liquid is 0.1-1.5%, and its mass percentage can be any specific value among 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, and 1.5wt%, or any value within the range of 0.1-1.5%.
[0019] In the present invention, the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is obtained by reacting the allyl epoxy polyoxyethylene polyether and the aminosilane coupling agent at 75-85°C for 2.5-3.5h. In the present invention, the molar ratio of the allyl epoxy polyoxyethylene polyether and the aminosilane coupling agent is 1.5-2.5:1. It can be understood that the molar ratio can be any specific value of 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1 or any value within the range of 1.5-2.5:1. Preferably, the molar ratio of the allyl epoxy polyoxyethylene polyether and the aminosilane coupling agent is 2.0-2.5:1.
[0020] In the present invention, in step (4), the water fiber opening treatment is specifically: water flow is uniformly sprayed on the cloth surface through a water needle plate with uniformly distributed circular nozzles to open the fibers. Preferably, in the water fiber opening treatment, the nozzle aperture is 1-2 mm and the pressure is 3-5 kg. The present invention first performs a water fiber opening treatment on the glass fiber cloth under low pressure to disperse the yarn bundles of the glass fiber cloth. At the same time, due to the low pressure, the hairiness of the glass fiber cloth is reduced, thereby improving the quality of the glass fiber cloth.
[0021] In the present invention, in step (4), the temperature of the primary drying is 125-135°C, and the time is 15-20s. It is understandable that the temperature of the primary drying can be any specific value among 125°C, 126°C, 127°C, 128°C, 129°C, 130°C, 131°C, 132°C, 133°C, 134°C, 135°C, or any value within the range of 125-135°C. The time of the primary drying can be any specific value among 15s, 16s, 17s, 18s, 19s, 20s, or any value within the range of 15-20s.
[0022] In the present invention, in step (4), the treatment liquid immersion treatment is specifically: completely immersing the glass fiber cloth in the treatment liquid. Preferably, the immersion time is 5-10 minutes. The purpose of this step is to allow the treatment liquid to fully immerse the internal pores of the fibers and between the fibers to ensure the interface bonding between the glass fiber cloth and the resin.
[0023] In the present invention, in step (4), the secondary drying temperature is 110-120°C and the time is 40-60s. It is understandable that the secondary drying temperature can be any specific value of 110°C, 111°C, 112°C, 113°C, 114°C, 115°C, 116°C, 117°C, 118°C, 119°C, 120°C or any value within the range of 110-120°C. The present invention controls the temperature of the secondary drying within the above range, which can minimize the moisture content while ensuring that the performance of the coupling agent remains stable.
[0024] In the present invention, in step (4), the fiber opening treatment of the treatment liquid is specifically as follows: the treatment liquid is evenly sprayed on the cloth surface through a water needle plate with evenly distributed circular nozzles to open the fibers. Preferably, in the fiber opening treatment of the treatment liquid, the nozzle aperture is 2-3 mm and the pressure is 2-3 kg. Since microbubbles will adhere to the fiber surface during the treatment liquid immersion treatment, these microbubbles will partially remain at the interface between the fiber and the resin to form a weak interface layer, resulting in interface defects and stress concentration, and reducing the bonding strength and ion migration resistance of the interface. Therefore, the present invention adds a fiber opening treatment step of the treatment liquid. After the fiber opening treatment by the treatment liquid, the microbubbles attached to the fiber surface will be greatly reduced, thereby further improving the interface bonding strength and ion migration resistance of the glass fiber cloth and the resin.
[0025] In the present invention, in step (4), the temperature of the three dryings is 110-120°C and the time is 40-60s. It is understandable that the temperature of the three dryings can be any specific value of 110°C, 111°C, 112°C, 113°C, 114°C, 115°C, 116°C, 117°C, 118°C, 119°C, 120°C or any value within the range of 110-120°C.
[0026] The present invention optimizes the post-treatment process of the glass fiber cloth. The glass fiber cloth after desizing is first subjected to water fiber opening treatment under low pressure. On the one hand, due to the low pressure, the hairiness of the glass fiber cloth is reduced; on the other hand, after the water fiber opening treatment, the yarn bundles of the glass fiber cloth are more dispersed, and the surface area is increased, which is convenient for the subsequent treatment liquid impregnation process to more fully impregnate the treatment liquid in the internal pores of the fiber and between the fibers. In addition, since microbubbles will be attached to the fiber surface during the impregnation process, these microbubbles will partially remain at the interface between the fiber and the resin, forming a weak interface layer, resulting in interface defects and stress concentration, and reducing the bonding strength and ion migration resistance of the interface. After the treatment liquid fiber opening treatment, the microbubbles attached to the fiber surface will be greatly reduced, thereby further improving the interface bonding strength and ion migration resistance of the glass fiber cloth and the resin.
[0027] According to another aspect of the present invention, there is also provided an ion migration resistant electronic grade glass fiber cloth prepared according to the above method.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention obtains a long-chain coupling agent by reacting an allyl epoxy polyoxyethylene polyether and an aminosilane coupling agent, and then compounding the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent and a phenyltrimethoxysilane coupling agent in proportion. The allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent has a long flexible molecular chain and a large number of active functional groups. The long flexible molecular chain can also be physically entangled at the interface. The large number of active functional groups further improves the interface bonding strength. The phenyltrimethoxysilane coupling agent has a short molecular chain and contains a phenyl group, which can better impregnate into the internal pores of the glass fiber. The two work synergistically, so that the interface bonding strength between the glass fiber cloth and the resin is high and the resin impregnation is good. The copper clad laminate prepared in this way has good resistance to ion migration and excellent heat resistance.
[0030] (2) The present invention further optimizes the post-processing process of glass fiber cloth. The desized glass fiber cloth is first subjected to water fiber opening treatment under low pressure. On the one hand, due to the low pressure, the hairiness of the glass fiber cloth is reduced; on the other hand, after the water fiber opening treatment, the yarn bundles of the glass fiber cloth are more dispersed, increasing the surface area, which is convenient for the subsequent treatment liquid impregnation process to more fully impregnate the treatment liquid into the internal pores of the fibers and between the fibers. In addition, since microbubbles will adhere to the fiber surface during the impregnation process, these microbubbles will partially remain at the interface between the fiber and the resin to form a weak interface layer, resulting in interface defects and stress concentration, and reducing the interface bonding strength and ion migration resistance. After the treatment liquid fiber opening treatment, the microbubbles attached to the fiber surface will be greatly reduced, thereby further improving the interface bonding strength and ion migration resistance of the glass fiber cloth and the resin. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0032] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0033] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0034] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0035] The present invention provides a method for preparing an ion migration resistant electronic grade glass fiber cloth, which is characterized by comprising the following steps:
[0036] (1) The sized warp yarns are evenly wound on the warp beam for sizing;
[0037] (2) Put the sized warp beam on the loom, insert the weft on the loom, and weave the rough glass fiber cloth according to the warp and weft density;
[0038] (3) desizing the crude glass fiber cloth at high temperature, and obtaining the desizing glass fiber cloth after cooling;
[0039] (4) subjecting the desized glass fiber cloth to water fiber opening treatment, primary drying, treatment liquid immersion treatment, secondary drying, treatment liquid fiber opening treatment and tertiary drying in sequence to obtain the ion migration resistant electronic grade glass fiber cloth; wherein the treatment liquid contains allyl epoxy polyoxyethylene polyether modified amino silane coupling agent and phenyl trimethoxy silane coupling agent in a mass ratio of 2-3:1.
[0040] In the present invention, the treatment liquid comprises, by mass percentage, 0.2-1.5% of allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent, 0.1-0.5% of phenyltrimethoxysilane coupling agent, 0.1-1.5% of acetic acid and the balance of water.
[0041] In the present invention, the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is obtained by reacting the allyl epoxy polyoxyethylene polyether and aminosilane coupling agent at 75-85° C. for 2.5-3.5 hours.
[0042] In the present invention, the molar ratio of the allyl epoxy polyoxyethylene polyether to the aminosilane coupling agent is 1.5-2.5:1.
[0043] In the present invention, the aminosilane coupling agent is 3-aminopropyltrimethoxysilane.
[0044] In the present invention, in step (3), the desizing temperature is 380-400° C. and the time is 30-40 min.
[0045] In the present invention, in step (4), the temperature of the first drying is 125-135°C, and the time is 15-20s; the temperature of the second drying is 110-120°C, and the time is 40-60s; the temperature of the third drying is 110-120°C, and the time is 40-60s.
[0046] In the present invention, in step (4), in the water fiber opening treatment, the nozzle aperture is 1-2 mm and the pressure is 3-5 kg.
[0047] In the present invention, in step (4), during the fiber opening treatment with the treatment liquid, the nozzle aperture is 2-3 mm and the pressure is 2-3 kg.
[0048] The present invention also provides an ion migration resistant electronic grade glass fiber cloth prepared according to the method.
[0049] The present invention will be described in detail below by way of examples, wherein Example 1 is the best example. It should be understood that the following examples are only used to further explain and illustrate the content of the present invention by way of example, and are not used to limit the present invention.
[0050] The chemical additives used in the examples and comparative examples of the present invention are all commercially available, and their specific information is as follows:
[0051] The warp yarn used was D450 and the weft yarn was G150, both of which were purchased from Henan Guangyuan New Materials Co., Ltd.; the warp density was 120 yarns / 25 mm, and the weft density was 64 yarns / 25 mm.
[0052] Allyl epoxy polyoxyethylene polyether: purchased from Aladdin Reagent Co., Ltd.; 3-aminopropyl trimethoxy silane coupling agent: purchased from Aladdin Reagent Co., Ltd.; phenyl trimethoxy silane coupling agent: purchased from Nanjing Quanxi New Materials Co., Ltd.; acetic acid: analytical grade, purchased from Aladdin Reagent Co., Ltd.; vinyl triethoxy silane: purchased from Nanjing Pinning Coupling Agent Co., Ltd.; hexadecyl trimethoxy silane coupling agent: purchased from Nanjing Quanxi New Materials Co., Ltd.
[0053] Example 1
[0054] The method for preparing an ion migration resistant electronic grade glass fiber cloth described in this embodiment comprises the following steps:
[0055] (1) The sizing machine is used to evenly apply the sizing agent to the warp yarns, and the sizing warp yarns are evenly wound around the warp beams for sizing;
[0056] (2) Put the sized warp beam on the loom, insert the weft on the loom, and weave the rough glass fiber cloth according to the warp and weft density;
[0057] (3) desizing the crude glass fiber cloth at 400° C. for 30 minutes, and obtaining a desizing glass fiber cloth after cooling;
[0058] (4) water is uniformly sprayed on the surface of the desized glass fiber cloth through a water jet plate with a uniformly distributed pore size of 2 mm to perform water fiber opening treatment, the pressure is 4 kg, and it is dried once at 130°C for 15 seconds, then the dried glass fiber cloth is completely immersed in part of the treatment liquid for 8 minutes, and it is dried twice at 120°C for 50 seconds, and then the other part of the treatment liquid is uniformly sprayed on the surface of the glass fiber cloth after the second drying through a water jet plate with a uniformly distributed pore size of 3 mm to perform treatment with the treatment liquid fiber opening treatment, the pressure is 2 kg, and it is dried three times at 120°C for 50 seconds to obtain the ion migration resistant electronic grade glass fiber cloth; wherein the treatment liquid comprises, by mass percentage, 1% allyl epoxy polyoxyethylene polyether modified amino silane coupling agent, 0.4% phenyl trimethoxy silane coupling agent, 0.5% acetic acid and the balance water.
[0059] The preparation method of the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent comprises the following steps:
[0060] Under stirring, 1 mol of 3-aminopropyltrimethoxysilane coupling agent was added to 2 mol of allyl epoxy polyoxyethylene polyether, and the mixture was stirred at 80° C. for 3 h to obtain the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent.
[0061] Example 2
[0062] The method for preparing an ion migration resistant electronic grade glass fiber cloth described in this embodiment comprises the following steps:
[0063] (1) The sizing machine is used to evenly apply the sizing agent to the warp yarns, and the sizing warp yarns are evenly wound around the warp beams for sizing;
[0064] (2) Put the sized warp beam on the loom, insert the weft on the loom, and weave the rough glass fiber cloth according to the warp and weft density;
[0065] (3) desizing the crude glass fiber cloth at 380° C. for 40 minutes, and cooling the desizing glass fiber cloth to obtain the desizing glass fiber cloth;
[0066] (4) water is uniformly sprayed on the surface of the desized glass fiber cloth through a water jet plate with a uniformly distributed pore size of 1 mm to perform water fiber opening treatment, the pressure is 5 kg, and it is dried once at 135° C. for 15 seconds, and then the dried glass fiber cloth is completely immersed in part of the treatment liquid for 5 minutes, and it is dried twice at 110° C. for 60 seconds, and then the other part of the treatment liquid is uniformly sprayed on the surface of the glass fiber cloth after the second drying through a water jet plate with a uniformly distributed pore size of 2 mm to perform treatment with the treatment liquid fiber opening treatment, the pressure is 3 kg, and it is dried three times at 110° C. for 60 seconds to obtain the electronic grade glass fiber cloth resistant to ion migration; wherein the treatment liquid comprises, by mass percentage, 1.5% allyl epoxy polyoxyethylene polyether modified amino silane coupling agent, 0.5% phenyl trimethoxy silane coupling agent, 1.5% acetic acid and the balance water.
[0067] The preparation method of the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent comprises the following steps:
[0068] Under stirring, 1 mol of 3-aminopropyltrimethoxysilane coupling agent was added to 2.5 mol of allyl epoxy polyoxyethylene polyether, and the mixture was stirred at 85° C. for 2.5 h to obtain the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent.
[0069] Example 3
[0070] The method for preparing an ion migration resistant electronic grade glass fiber cloth described in this embodiment comprises the following steps:
[0071] (1) The sizing machine is used to evenly apply the sizing agent to the warp yarns, and the sizing warp yarns are evenly wound around the warp beams for sizing;
[0072] (2) Put the sized warp beam on the loom, insert the weft on the loom, and weave the rough glass fiber cloth according to the warp and weft density;
[0073] (3) desizing the crude glass fiber cloth at 380° C. for 40 minutes, and cooling the desizing glass fiber cloth to obtain the desizing glass fiber cloth;
[0074] (4) water is uniformly sprayed on the surface of the desized glass fiber cloth through a water jet plate with a uniformly distributed pore size of 2 mm to perform water fiber opening treatment, the pressure is 4 kg, and it is dried once at 125° C. for 20 seconds, and then the dried glass fiber cloth is completely immersed in part of the treatment liquid for 10 minutes, and it is dried twice at 110° C. for 40 seconds, and then the other part of the treatment liquid is uniformly sprayed on the surface of the glass fiber cloth after the second drying through a water jet plate with a uniformly distributed pore size of 3 mm to perform treatment with the treatment liquid fiber opening treatment, the pressure is 2 kg, and it is dried three times at 110° C. for 40 seconds to obtain the electronic grade glass fiber cloth resistant to ion migration; wherein the treatment liquid comprises, by mass percentage, 0.2% allyl epoxy polyoxyethylene polyether modified amino silane coupling agent, 0.1% phenyl trimethoxy silane coupling agent, 0.1% acetic acid and the balance water.
[0075] The preparation method of the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent comprises the following steps:
[0076] Under stirring, 1 mol of 3-aminopropyltrimethoxysilane coupling agent was added to 1.5 mol of allyl epoxy polyoxyethylene polyether, and the mixture was stirred at 75° C. for 3.5 hours to obtain the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent.
[0077] Example 4
[0078] The method for preparing an ion migration resistant electronic grade glass fiber cloth described in this embodiment comprises the following steps:
[0079] (1) The sizing machine is used to evenly apply the sizing agent to the warp yarns, and the sizing warp yarns are evenly wound around the warp beams for sizing;
[0080] (2) Put the sized warp beam on the loom, insert the weft on the loom, and weave the rough glass fiber cloth according to the warp and weft density;
[0081] (3) desizing the crude glass fiber cloth at 400° C. for 30 minutes, and obtaining a desizing glass fiber cloth after cooling;
[0082] (4) water is uniformly sprayed on the surface of the desized glass fiber cloth through a water jet plate with a uniformly distributed pore size of 2 mm to perform water fiber opening treatment, the pressure is 4 kg, and it is dried once at 130°C for 15 seconds, then the dried glass fiber cloth is completely immersed in part of the treatment liquid for 8 minutes, and it is dried twice at 120°C for 50 seconds, and then the other part of the treatment liquid is uniformly sprayed on the surface of the glass fiber cloth after the second drying through a water jet plate with a uniformly distributed pore size of 3 mm to perform treatment with the treatment liquid fiber opening treatment, the pressure is 2 kg, and it is dried three times at 120°C for 50 seconds to obtain the electronic grade glass fiber cloth resistant to ion migration; wherein the treatment liquid comprises, by mass percentage, 0.6% allyl epoxy polyoxyethylene polyether modified amino silane coupling agent, 0.3% phenyl trimethoxy silane coupling agent, 1% acetic acid and the balance water.
[0083] The preparation method of the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent comprises the following steps:
[0084] Under stirring, 1 mol of 3-aminopropyltrimethoxysilane coupling agent was added to 2 mol of allyl epoxy polyoxyethylene polyether, and the mixture was stirred at 80° C. for 3 h to obtain the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent.
[0085] Comparative Example 1
[0086] The preparation method of the glass fiber cloth in this comparative example is exactly the same as that in Example 1, except that the treatment liquid includes, by mass percentage, 2% allyl epoxy polyoxyethylene polyether modified amino silane coupling agent, 0.4% phenyl trimethoxy silane coupling agent, 0.5% acetic acid and the balance water.
[0087] Comparative Example 2
[0088] The preparation method of the glass fiber cloth in this comparative example is exactly the same as that in Example 1, except that the treatment liquid includes, by mass percentage, 0.4% allyl epoxy polyoxyethylene polyether modified amino silane coupling agent, 1.4% phenyl trimethoxy silane coupling agent, 0.5% acetic acid and the balance water.
[0089] Comparative Example 3
[0090] The preparation method of the glass fiber cloth of this comparative example is exactly the same as that of Example 1, except that in step (4), no treatment liquid fiber opening treatment is performed, that is, step (4) is: water is uniformly sprayed on the surface of the desized glass fiber cloth through a water jet plate with circular nozzles uniformly distributed with an aperture of 2 mm to perform water fiber opening treatment, the pressure is 4 kg, and the glass fiber cloth is dried once at 130° C. for 15 seconds, and then the dried glass fiber cloth is completely immersed in part of the treatment liquid for 8 minutes, and is dried twice at 120° C. for 50 seconds to obtain the electronic grade glass fiber cloth resistant to ion migration; wherein the treatment liquid comprises, by mass percentage, 1% of allyl epoxy polyoxyethylene polyether modified amino silane coupling agent, 0.4% of phenyl trimethoxy silane coupling agent, 0.5% of acetic acid and the balance of water.
[0091] Comparative Example 4
[0092] The preparation method of the glass fiber cloth of this comparative example is exactly the same as that of Example 1, except that the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is replaced by an equal mass of hexadecyltrimethoxysilane coupling agent.
[0093] Comparative Example 5
[0094] The preparation method of the glass fiber cloth of this comparative example is exactly the same as that of Example 1, except that the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is replaced by an equal mass of 3-aminopropyl trimethoxysilane coupling agent.
[0095] Comparative Example 6
[0096] The preparation method of the glass fiber cloth in this comparative example is exactly the same as that in Example 1, except that the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is replaced by an equal mass of vinyl triethoxy silane.
[0097] Performance Testing
[0098] The 500 m finished glass fiber cloths prepared in Examples 1-4 and Comparative Examples 1-6 were subjected to performance tests according to the following testing methods. The specific test results are shown in Table 1.
[0099] (1) Resin wettability test: Dissolve epoxy resin in acetone and inject the mixed solution into a syringe. Take a 10×10 cm glass fiber cloth sample and place it on a horizontal surface. Push 0.2 ml of the epoxy resin acetone mixed solution out of the syringe so that the surface of the glass fiber cloth contacts the droplet of the mixed solution. After the droplet falls on the cloth surface, the contact angle is obtained. The angle between the tangent line of the droplet surface of the epoxy resin acetone mixed solution and the reference line of the glass fiber cloth surface is the contact angle.
[0100] (2) Whether there is hairiness: Observe the surface of the glass fiber cloth with the naked eye to see if there is any hairiness.
[0101] (3) Tensile strength: Take a sample of 2.54 cm × 15 cm in size and use a strength tester to test the tensile strength of the glass fiber cloth in the warp and weft directions (if testing the warp tensile strength, sample according to the length in the warp direction; if testing the weft tensile strength, sample according to the length in the weft direction).
[0102] Table 1 Performance of glass fiber cloth of Examples 1-4 and Comparative Examples 1-6
[0103] .
[0104] It can be seen from Table 1 that the glass fiber cloth in Examples 1-4 has basically no hairiness, a small contact angle, and a high warp tensile strength, indicating that the preparation method of the present invention can significantly improve the interfacial bonding between the glass fiber cloth and the resin and the wettability of the resin. In Comparative Examples 1 and 2, the mass ratio of the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent and the phenyltrimethoxysilane coupling agent is higher or lower, and the contact angle of the obtained glass fiber cloth becomes larger and a small amount of hairiness is produced, indicating that the resin wettability and interfacial bonding strength of the glass fiber cloth are reduced. The preparation method in Comparative Document 3 lacks the step of fiber opening treatment with the treatment liquid, and the resin wettability and interfacial bonding strength of the obtained glass fiber cloth are also significantly reduced. In Comparative Examples 4-6, the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is replaced with other types of coupling agents, and the resin wettability and interfacial bonding strength of the obtained glass fiber cloth are reduced to varying degrees.
[0105] Copper clad laminates were prepared using the electronic grade glass fiber cloths prepared in Examples 1-4 and Comparative Examples 1-6 of the present invention, and performance tests were performed on the copper clad laminates. The test results are shown in Table 2.
[0106] (1) Dielectric properties: Tested in accordance with IEC61189-2-719-2016 standard.
[0107] (2) Ion migration resistance: The sample is made into a double-sided PCB test board with a minimum hole-to-wall spacing of 0.3mm. The sample board is placed in a 105°C oven for 6 hours, then placed in an environment of 23°C temperature and 50% humidity for 24 hours, and then placed in an environment of 85°C, 85% humidity and 100V. As time goes by, the board hole spacing gradually fails in insulation. When the detected resistance value is less than 1 megohm, it is considered a failure. When the number of failure points does not exceed 50% after 1000 hours, it is considered a pass.
[0108] (3) Peel strength: The peel strength performance of the above copper clad laminates was tested according to the testing standard GB / T36476-2018.
[0109] (4) Heat resistance: The sample that has been steamed in a PCT high-pressure cooking pot for 4 hours is placed in a tin furnace at a temperature of 288°C for heat resistance testing. At the same time, a stopwatch is used to time the sample. The sample is immersed in the tin liquid for 300 seconds to observe whether the sample bursts (bubbles). If there is a burst (bubbling), it means that the plate has been delaminated and failed.
[0110] Table 2 Performance of copper clad laminates prepared from glass fiber cloth of Examples 1-4 and Comparative Examples 1-6
[0111] .
[0112] It can be seen from Table 2 that the dielectric constant (1GHz) of the copper-clad laminate prepared using the glass fiber cloth in Examples 1-4 of the present invention as raw material is lower, the dielectric loss (1GHz) is also lower, and the ion migration resistance and heat resistance are excellent. In Comparative Examples 1 and 2, the mass ratio of the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent and the phenyltrimethoxysilane coupling agent is higher or lower, and the dielectric constant and dielectric loss of the corresponding copper-clad laminate are increased, and the ion migration resistance is reduced, indicating that the dielectric properties are deteriorated. The preparation method in Comparative Document 3 lacks the step of fiber opening treatment with the treatment liquid, and the dielectric constant and dielectric loss of the corresponding copper-clad laminate are significantly increased, and the ion migration resistance is significantly reduced. In Comparative Examples 4-6, the allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is replaced with other types of coupling agents, and the dielectric properties and heat resistance of the corresponding copper-clad laminate are reduced to varying degrees.
[0113] It can be seen that the present invention obtains a long-chain coupling agent by reacting allyl epoxy polyoxyethylene polyether and amino silane coupling agent, and then compounding the allyl epoxy polyoxyethylene polyether modified amino silane coupling agent and phenyl trimethoxy silane coupling agent in proportion. The allyl epoxy polyoxyethylene polyether modified amino silane coupling agent has a long flexible molecular chain and a large number of active functional groups. The long flexible molecular chain can also generate physical entanglement at the interface, and the large number of active functional groups further improves the interface bonding strength; and the phenyl trimethoxy silane coupling agent has a short molecular chain and contains a phenyl group, which can be better impregnated into the internal pores of the glass fiber. The two synergistically enhance the interface bonding strength between the glass fiber cloth and the resin, so that the resin impregnation is good, and the copper clad laminate prepared thereby has good resistance to ion migration and excellent heat resistance.
[0114] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing an ion migration resistant electronic grade glass fiber cloth, characterized in that: The following steps are involved: (1) The sized warp yarns are evenly wound on the warp beam for sizing; (2) Put the sized warp beam on the loom, insert the weft on the loom, and weave the rough glass fiber cloth according to the warp and weft density; (3) desizing the crude glass fiber cloth at high temperature, and obtaining the desizing glass fiber cloth after cooling; (4) subjecting the desized glass fiber cloth to water fiber opening treatment, primary drying, treatment liquid immersion treatment, secondary drying, treatment liquid fiber opening treatment and tertiary drying in sequence to obtain the ion migration resistant electronic grade glass fiber cloth; wherein the treatment liquid contains allyl epoxy polyoxyethylene polyether modified amino silane coupling agent and phenyl trimethoxy silane coupling agent in a mass ratio of 2-3:1; The allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent is obtained by reacting allyl epoxy polyoxyethylene polyether and aminosilane coupling agent at 75-85° C. for 2.5-3.5 hours; In step (4), the fiber opening treatment with the treatment liquid is specifically as follows: the treatment liquid is uniformly sprayed onto the fabric surface through a water needle plate with uniformly distributed circular nozzles to open the fabric.
2. The method for preparing an ion migration resistant electronic grade glass fiber cloth according to claim 1, characterized in that: The treatment liquid comprises, by mass percentage, 0.2-1.5% of allyl epoxy polyoxyethylene polyether modified aminosilane coupling agent, 0.1-0.5% of phenyltrimethoxysilane coupling agent, 0.1-1.5% of acetic acid and the balance of water.
3. The method for preparing an ion migration resistant electronic grade glass fiber cloth according to claim 1, characterized in that: The molar ratio of the allyl epoxy polyoxyethylene polyether to the aminosilane coupling agent is 1.5-2.5:
1.
4. The method for preparing an ion migration resistant electronic grade glass fiber cloth according to claim 1, characterized in that: The aminosilane coupling agent is 3-aminopropyltrimethoxysilane.
5. The method for preparing an ion migration resistant electronic grade glass fiber cloth according to claim 1, characterized in that: In step (3), the desizing temperature is 380-400°C and the desizing time is 30-40 minutes.
6. The method for preparing an ion migration resistant electronic grade glass fiber cloth according to claim 1, characterized in that: In step (4), the temperature of the first drying is 125-135°C, and the time is 15-20s; the temperature of the second drying is 110-120°C, and the time is 40-60s; the temperature of the third drying is 110-120°C, and the time is 40-60s.
7. The method for preparing an ion migration resistant electronic grade glass fiber cloth according to claim 1, characterized in that: In step (4), during the water fiber opening treatment, the nozzle aperture is 1-2 mm and the pressure is 3-5 kg.
8. The method for preparing an ion migration resistant electronic grade glass fiber cloth according to claim 1, characterized in that: In step (4), during the fiber opening treatment with the treatment liquid, the nozzle aperture is 2-3 mm and the pressure is 2-3 kg.
9. An ion migration resistant electronic grade glass fiber cloth prepared according to the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
A method for producing thin electronic-grade glass fiber cloth
CN115354494B
Electronic grade glass fiber cloth treating agent and glass fiber cloth manufactured by treating agent
CN109505125A
Preparation process of high-performance electronic-grade glass fiber cloth
CN112626854A